Hubungan Karakteristik Pasien dengan Tingkat Kepuasan Pelayanan pada Pasien Operasi Sub Bagian Fasial Plastik dan Bedah Rekonstruksi Bagian THT-KL RSUP Dr. M. Djamil Tahun 2019 - Fauzan Junanda Putra; Al-Hafiz Al-Hafiz; Firdawati Firdawati (Jurnal Ilmu Kesehatan Indonesia, 2021)
Hospitals play an important role in providing quality public services. The success of a hospital in providing services can be seen from the performance of health care provider and patient satisfaction. Patient satisfaction is the evaluative, emotional or affective response of the patient to the service provided by the health care provider and the expectation of the service. The satisfaction of each patient can be different depending on the expectations and reality obtained. This can be caused by several factors such as age, gender, occupation and education. This study was conducted to determine the relationship of these patient characteristics with the level of patient service satisfaction in the plastic facial and reconstructive surgery division of ENT department of Dr. M. Djamil hospital. This type of research is analytic research with cross sectional design. Respondents in this study were 37 people. Sampling was done using a purposive sampling method. This study used satisfaction questionnaires and medical record as an research instrument. The results showed that there were more subjects in the old adult age category (56.76%), female (51.35%), had a job (51.35%), had a high education (81.08%), and non PBI membership status (56,8%). The results of bivariate analysis showed that there was no relationship between age, sex, education and occupation with the level of satisfaction. P values ​​obtained respectively p = 0.366, p = 0.692, p = 0.554 and p = 0.845. Whereas there are relationship between patient health assurance membership status with patient satisfaction by p values 0,033. Conclusion: that there is no relationship between patient characteristics with the level of service satisfaction in patients in the plastic facial and reconstructive surgery division in the ENT department of Dr. M. Djamil hospital except for health assurance membership status. Keywords: Education, Occupation, Health Assurance Membership Status, Satisfaction